Oxocarbon Acids and their Derivatives in Biological and Medicinal Chemistry - Ratto, Amanda; Honek, John F. (Current Medicinal Chemistry, 2024)
The biological and medicinal chemistry of the oxocarbon acids 2,3- dihydroxycycloprop-2-en-1-one (deltic acid), 3,4-dihydroxycyclobut-3-ene-1,2-dione (squaric acid), 4,5-dihydroxy-4-cyclopentene-1,2,3-trione (croconic acid), 5,6-dihydroxycyclohex- 5-ene-1,2,3,4-tetrone (rhodizonic acid) and their derivatives is reviewed and their key chemical properties and reactions are discussed. Applications of these compounds as potential bioisosteres in biological and medicinal chemistry are examined. Reviewed areas include cell imaging, bioconjugation reactions, antiviral, antibacterial, anticancer, enzyme inhibition, and receptor pharmacology.
Keywords: bioisosteres